Sandalodesmus joachimadisi n. sp., the first Chelodesmidae member from Uruguay with an updated key to species of the genus (Diplopoda: Polydesmida) - Rojas-Buffet, Carolina; Bouzan, Rodrigo Salvador; Sierwald, Petra; Brescovit, Antonio Domingos; Simó, Miguel (Zootaxa, 2022)
A new species of Chelodesmidae is described from northern Uruguay, Sandalodesmus joachimadisi n. sp. The new species differs from other congeners by particular features of the gonopods. Sandalodesmus joachimadisi n. sp. belongs to the iguazuensis species group. Photographs of the new species, data on its natural history and a geographic distribution map of all Sandalodesmus species are presented. A key to the species of Sandalodesmus is provided. The taxonomic relationships with other species of the genus are discussed.